Penerapan Pembelajaran Mendalam (Deep Learning) Berbasis Teori Belajar Humanisme untuk Meningkatkan Kemampuan Belajar Peserta Didik - Simamora, Rona Marisa; Sitepu, Edy Petra Kristian; Sinaga, Rianda; Lahagu, Kristiani; Sitorus, Juriani; Manik, Efron; Pangaribuan, Firman (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of implementing deep learning based on humanistic learning theory on the learning abilities of students at Methodist Kuala Private Junior High School. This study uses a quasi-experimental design with a pretest-posttest control group design. The research subjects consist of two classes, namely class VIII-1 as the experimental class and class VIII-2 as the control class, each consisting of 32 students. The research instrument consists of a learning ability test administered to both groups before (pretest) and after the intervention (posttest). The data obtained were analyzed using a t-test to examine differences in learning outcomes between groups, as well as N-Gain calculations to determine the level of improvement in learning ability. The results showed that the initial abilities of the two groups were relatively equal. However, after the treatment, the experimental class achieved higher posttest scores (M = 87.5; SD = 7.16) with an N-Gain of 0.71 (high category), compared to the control class (M = 82.3; SD = 7.37) with an N-Gain of 0.59 (moderate category). The t-test results showed a significant difference (p < 0.05) in learning outcomes after the treatment. These findings indicate that humanistic theory-based deep learning is effective in improving students' learning abilities while creating an empathetic and supportive learning environment.